Relationships Between Heart Rate Variability, Occupational Performance, and Fitness for Tactical Personnel: A Systematic Review - Tomes, Colin; Schram, Ben; Orr, Robin (Frontiers in Public Health, 2020)
Objectives: Heart Rate Variability has gained substantial interest in both clinical and athletic settings as a measurement tool for quantifying autonomic nervous system activity and psychophysiological stress. However, its uses in tactical work settings, such as military, police and firefighting environments, remain controversial. Given the physical, mental and emotional stress public safety personnel face both operationally and in training, heart rate variability measurement may be key in promoting their health, safety and operational effectiveness. Methods: This study identified, critically appraised, and summarized primary studies investigating relationships between heart rate variability and outcomes of interest to tactical personnel. Key literature databases were searched, and quality assessment checklists were applied to analyze retained literature. The results of the screening and assessment processes, along with key data extracted from each study were summarized and tabulated. Research gaps were also identified to improve to how tactical personnel and health or performance providers may best utilize heart rate variability to monitor or promote personnel health and performance, and thereby facilitate public safety. Results: Twenty studies were included and were all of generally high quality. Cohort size, length of follow-up, measurement objectives, data acquisition, and data analysis all varied considerably across studies, precluding meta-analysis. However, study results correlating heart rate variability and relevant outcomes indicated that overall, heart rate variability is an effective indicator of key fitness and performance elements in the tactical work setting. Conclusions: Heart rate variability can be an effective health and performance tool in tactical work environments. However, measurement methods must be carefully selected and applied. Further research is required to understand causal relationships. Specifically, larger cohort inclusion and the isolation and study of specific variables unique to public safety work and training may improve the effectiveness of heart rate variability measurement to provide meaningful information to end users and providers.